Effect of Previous Respiratory Syncytial Virus Infection on Murine Immune Responses to F and G Protein-Containing Virus-Like Particles - McGinnes Cullen, Lori (J Virol, 2019)
Most individuals are infected with respiratory syncytial virus (RSV) by age two, but infection does not result in long-term protective immunity to subsequent infections. Previous RSV infection may, however, impact responses to an RSV vaccine. The goal of these studies was to explore the effect of previous RSV infection on murine antibody responses to RSV F and G protein-containing virus-like particles (VLP), comparing responses to those resulting from VLP immunization of RSV-naive animals. These studies showed that after RSV infection, immunization with a single dose of VLPs containing a conformation-stabilized prefusion F protein stimulated high titers of neutralizing antibodies (NA), while an immunization with post-F-containing VLPs or a second RSV infection only weakly stimulated NA, even though total anti-F protein IgG antibody levels in both VLP-immunized animals were similar. Furthermore, single pre-F or post-F VLP immunization of animals previously infected (primed) with RSV resulted in total anti-F antibody titers that were 10- to 12-fold higher than titers after a VLP prime and boost of RSV-naive animals or after two consecutive RSV infections. The avidities of serum antibodies as well as numbers of splenic B cells and bone marrow cells after different immunization protocols were also assessed. The combined results show that RSV infection can quite effectively prime animals for the production of protective antibodies that can be efficiently activated by a pre-F VLP boost but not by a post-F VLP boost or a second RSV infection. IMPORTANCE Humans may experience repeated infections caused by the same serotype of respiratory syncytial virus (RSV), in contrast to infections with most other viruses, indicating that immune memory responses to RSV are defective. However, the effects of any residual but nonprotective immunity on responses to RSV vaccines are not clear. This study demonstrates that a VLP vaccine candidate containing a stabilized prefusion F protein can robustly stimulate protective immunity in animals previously infected with RSV, while a second RSV infection or a postfusion F-containing VLP cannot. This result shows that a properly constructed immunogen can be an effective vaccine in animals previously infected with RSV. The results also suggest that the defect in RSV memory is not in the induction of that memory but rather in its activation by a subsequent RSV infection.